The 2nd International Conference on Agricultural and Biological Sciences (ABS 2016). (October 2016) - Pei, Lei; Wang, Zhenhua; Zhang, Jinzhu; Li, Wenhao; Ting, Adeline; Chow, Yiing; Rahman, Sadequr; Wei, Rongchang; Hu, Zhang; Li, Sidong; Li, Chuyan; Li, Zijuan; et al.
Table of contents 01 The influence of soil salt content on the photosynthetic characteristics of spring wheat with trickle irrigation Lei Pei, Zhenhua Wang, Jinzhu Zhang, Wenhao Li 02 Comparing growth of fast-growing and slow-growing endophytes in plants via ergosterol quantification Adeline SY Ting, Yiing Y Chow, Sadequr Rahman 03 Transcriptome and digital gene expression analysis identifies putative triterpene saponin-biosynthetic genes ofPanax notoginseng Rongchang Wei 04 Chitosan-assisted isolation and antioxidant evaluation of flavonoids fromSophora japonica L. Zhang Hu, Sidong Li, Chuyan Li, Zijuan Li 05 Two kinds of new characteristics of the ektexine ornamentation of ginkgo pollen Guoxia Wang, Yuzhen Yang, Gang Chen, Qing Luo 06 Analysis of nutrient and medicinal ingredients of Ginkgo pollen in different regions Guoxia Wang, Ruixia Liu, Yuzhen Yang, Lipei Chen 07 Photosynthetic performance of greening seedlings of seven species to drought stress Zhiyang Lie, Tongtong Zhou, Weilong Huang, Li Xue 08 Changes of fluorescence parameters of greening seedlings of seven species under drought stress Jie Li, Zhuomin Wang, Li Xue 09 Mammalian sex hormone affects regeneration capacity and enzymes activity of Triticale L in vitro culture Ismail Bezirganoglu, Pınar Uysal 10 Fractional Fourier entropy increases the recognition rate of fruit type detection Shuihua Wang, Zhihai Lu, Jiquan Yang, Yudong Zhang, John Liu, Ling Wei, Shufang Chen, Preetha Phillips, Zhengchao Dong 11 Banana-peanut intercropping reducesFusarium wilt disease in banana from enhancing soil bacterial microorganisms and leaf nutrition Hong Li, Xutong Wang, Fengliang Zhao, Guisheng Yang 12 Manganese stress impairs stem ureide nitrogen fixation in yardlong-bean plants in the acidic environment Hong Li 13 A new pest control method forRhytidodera bowringii Larvae Haijie Huang, Li Zhao, Weijian Huang, Jinhui Wang, Zhongrun Zhang 14 Research on the seed-like Fruits of Subg. Sclarea ofSalvia of Labiatae in China Xiaojuan Li, Ning Xu, Guofu Zhou, Ming Wan, Qi Lin, Fanyun Meng, Jianxiu Li 15 Three pulling resistance models of pioneer plant in landslide area Yichang Chen, Koayung Yu, Chunpin Chang 16 The comparison of physiological and biochemical mechanisms ofReaumuria soongorica andSalsola passerine in different growth pattern Zijuan Zhou, Peixi Su, Rui Shi, Tingting Xie 17 Resources use efficiency of the cosmopolitan plantPotentilla anserina L. in different alpine habitats in China Rui Shi, Peixi Su, Zijuan Zhou 18 Cloning of PPDK gene fromRed Amaran and transformation ofAlfalfa Xuelan Liu, Yan Zhang, Xiangfa Wei 19 Variation and cluster analysis of morphological characters and nutrient content ofChucrasia tabularis seed Chong Wu, Yanlei Yin, Lijuan Feng, Xuemei Yang, Fei Wang 20 Effect of the planting density of the areca nut on the growth of intercropped Vanilla Hua Wang, Huifa Zhuang, Zihui Zhu, Hui Wang